Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Vario - Lestiowati, Riris (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2018)
Inadequate public transportation, both in cities and villages, makes people prefer to use more efficient personal transportation. The increasing need and interest of the Indonesian people towards transportation which is fast, cheap and easy to use makes motorbikes preferred by the public to carry out daily activities. For this reason, it is a duty for the motorcycle industry to provide a variety of products and their choices to the public. This study intends to find out how much influence the brand image and quality of Honda Vario Matic products on consumer purchasing decisions. The method used in this study is quantitative, with an explanatory technique, this study applied a cross sectional research design. The research findings show that 1) the brand image of Honda Vario motorcycle is good and inherent in the minds of consumers, seen based on the results of the total calculation of each dimension of attributes, benefits, and overall evaluation. 2) product brand image and product quality have a significant influence on purchasing decisions. However, on the level and consistency dimensions, Honda must make improvements to the quality of its product.